Efeito da vitamina C e triptofano no desempenho, comportamento e parâmetros de estresse de frangos de corte - Aoyagi, Mônica Megumi [UNESP] (2015)
The study aimed to evaluate the effect of vitamin C and tryptophan supplementation on growth performance and stress parameters of broiler chickens raised in high stocking densities. An experiment was realized in a completely randomized design in a factorial arrangement 2 x 5 + 1 (vitamin C: 0 and 250 mg/kg of the diet; tryptophan: 100%; 125%; 150%; 175% and 200% of the recommendations associated to high stocking densities (17 birds/m²) and the negative control, diet without vitamin C + tryptophan according to the requirements, associated to low stocking density (12 birds/m²), with six replicates each. Growth performance variables analyzed were: body weight, weight gain, feed intake, feed conversion ratio, viability and productive efficiency index. Stress parameters measured were: serum glucose, heterophil: lymphocyte ratio, cholesterol, triglycerides, uric acid, VLDL, urofaecal corticosterone metabolites and antibody titers against NewCastle disease (P> 0,05). Growth performance is affected negatively by high stocking density. The feed conversion ratio of the broilers that received VC in the diet where improved (P< 0,05) compared with the unsupplemented ones. Vitamin C and tryptophan did not affect chicken immune response or biochemical blood parameters P> 0,05). The dosage of urofecal corticosterone metabolites for Enzyme immunoassay technique is adequate for noninvasive assessment of stress in broilers. Tryptophan supplementation in 200% associated with vitamin C was efficient to reduce stress caused by stocking density and can be indicated to broiler production promoting an improvement on the chicks welfare